Community Empowerment: A New Approach for the Sustainable Maintenance and Management of Chinese Historical Dwellings - Zhou, Fengyi; Buranaut, Isarachai (Journal of Community Development Research (Humanities and Social Sciences), 2024)
This research focuses on the Jianchuan Ancient City Historical and Cultural District. The aim of the study is to investigate and analyze the effective behaviors and implementation limitations of residents in the self-management and maintenance of historical dwellings. It also explores how the self-management and maintenance of historical dwellings benefit residents and the role these benefits play in the sustainable maintenance and management of historical dwellings. The development level of community empowerment practices in the area, along with the degree of community empowerment, are analyzed in this study, and suggestions are proposed for coping with limitations based on relevant successful cases to promote a sound community empowerment mechanism for the management and protection of historical dwellings. The study revealed that residents’ long-term proactive maintenance behavior significantly extended the lifespan of historical dwellings and maintained the city’s historical pattern. The need to repair wooden buildings has stimulated the development of local employment and traditional crafts. Residents were also found to play an important role in cultural dissemination and heritage research, establishing a preliminary collaborative relationship with the government, achieving a decentralization and proactive response, indicating the gradual development of the local community empowerment mechanism to a higher level, and demonstrating greater potential. The study findings also revealed the limitations of residents in terms of insufficient professional knowledge, financial constraints, and differences in investment within the community, posing potential challenges to improving community empowerment mechanisms and achieving the sustainable maintenance and management of historical residents. This study proposes the establishment of an architectural heritage to protect funds and organize professional training and lectures while providing historical dwelling archives and repair guidelines to ensure the autonomy, effectiveness, and sustainability of residents’ participation in the maintenance and management of historical dwellings. Keywords:   Community Empowerment, Historical Dwellings, Sustainable, Self-management and Maintenance Behavior, Community Empowerment Mechanism